Local temperature variation in Shillong area - MUKHERJEE, A. K. (MAUSAM, 1965)
Parry's (1956) and Lysack's (1957) conclusion that substantial local variations, occur due to relief of the place has been tested for local temperature variations in Shillong area for the Winter season for the years 1960-62. The variation of minimum temperature is more pronounced than the maximum temperature. Parry concluded that the influence of relief win be observed when the range of altitude of observatories recording local variation of temperature is small. the present study indicates that this variation is observable even where the range of altitude is of the order of 2000 ft.